Gender Performance and Identity Issues in “Ministry of Utmost Happiness” - Manzoor, Hunny; Sarfraz, Saima; Haider, Jawad (Annals of Human and Social Sciences, 2025)
This research examines The Ministry of Utmost Happiness by Arundhati Roy through Judith Butler's concept of gender performativity. The objective is to explore how gender is constructed and performed in the novel, particularly through the transformation of Aftab into Anjum, a hermaphrodite character struggling with identity. The study builds on Butler’s theory, which challenges the fixed nature of gender, and analyzes how Roy presents identity crises and gender troubles. Using a qualitative textual analysis methodology, the research critically engages with Anjum’s journey, highlighting performative aspects of gender. The findings suggest that Roy challenges traditional gender binaries, emphasizing fluidity and social construction. The study recommends further exploration of gender performativity in South Asian literature to deepen the discourse on identity. While limited to a single novel, this research contributes to understanding gender through literary representation.